Use of Blood Glucose Meters Featuring Color Range Indicators Improves Glycemic Control in Patients With Diabetes in Comparison to Blood Glucose Meters Without Color (ACCENTS Study) - Grady, Mike (J Diabetes Sci Technol, 2018)
BACKGROUND: The ability of patients to improve glycemic control depends partly on their ability to interpret and act on blood glucose results. We investigated whether switching people with diabetes to blood glucose meters (BGMs) featuring a color range indicator (CRI) could improve glycemic control compared to remaining on their current BGM without color. METHODS: 163 adults with type 1 (T1D) or type 2 diabetes (T2D) and a hemoglobin A1c (A1c) of 7.5-11% were randomized to: One Touch Verio™ (Verio), OneTouch Verio Flex™ (Flex), or controls remaining on their current BGM. Diabetes nurses had standard conversations about diabetes management with all subjects at baseline. No changes in medication, insulin dosing, or SMBG frequency were recommended. RESULTS: After 12 weeks, subjects who switched to Verio or Flex meters with CRI (n = 108) had a mean change in A1c 0.36% lower than controls (n = 55) (P = .017). A1c reductions were greatest in T1D subjects (n = 45), with a decrease of 0.50% (P = .004). T1D subjects using Verio meters (n = 25) contributed a 0.59% reduction compared to controls (P < .008), whereas T1D subjects using Flex meters (n = 20) had a clinical meaningful reduction in A1c of 0.40% without reaching statistical significance (P > .05). Verio and Flex users reported taking more action and easier understanding of diabetes management compared to previous BGMs. CONCLUSIONS: This study demonstrated that switching patients to BGMs featuring a CRI resulted in improvements in glycemic control compared to subjects using currently marketed BGMs that do not use a CRI. Registration: Clinicaltrials.gov NCT02929654 https://clinicaltrials.gov/ct2/show/NCT02929654